Pengembangan Bahan Ajar Menulis Fabel dengan Model Sinektik pada Peserta Didik Kelas VII SMP Muhammadiyah 1 Balikpapan - Muhammad Reza; Yusak Hudiyono; Masrur Yahya (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
Learning method, especially at fabel writing is less less variative; as a result, learning process cannot explore students’ writing skill. Therefore, the writer found that it needs to do the synectics learning method development in writing skill learning. This research purpose is to develop the synectics method development in writing learning process. This research uses research and Development (R&D) method, which is stated by Brog and Gall that it consists of ten steps of source development, which in this research, is VII grade students of SMP Muhammadiyah 1 Balikpapan. Data collection is done by doing the questionnaire, observing, interviewing and documenting. This learning method development is declared very feasible by three validators; material expert validator, media expert validator and learning pratitioner. Based on test result, the synectics model can imrpove the students’ score through the test process. The observation result of the learning activity is done by observer I and II and is declared very good.